Comparison of high resolution hydrodynamic model outputs with in-situ Argo profiles in the Ionian Sea - KASSIS, D.; KORRES, G.; KONSTANTINIDOU, A.; PERIVOLIOTIS, L. (Mediterranean Marine Science, 2017)
In-situ monitoring is an essential component for the development of hydrodynamic numerical models. Argo expansion into marginal seas has enabled the advancement of high resolution regional nested models through initialization, assimilation and validation processes. The SANI (Southern Adriatic-Northern Ionian) hydrodynamic model is a regional nested model producing high resolution outputs for the period 2008-2012. For the corresponding time period, 21 free drifting Argo floats recorded Temperature –Salinity (T/S) profiles throughout the region. This study presents the inter-comparison of the two data sets whilst noting interesting aspects of the model performance regarding the representation of the major water masses characteristics of the SANI area. Aside from the inter-comparison in a basin’s scale, a spatio-temporal analysis is also performed. The results indicate an adequate response of the model simulations regarding the basic hydrographic features of the region. Nevertheless, important differences are highlighted mainly in the upper and deep layers of the study area. At a regional scale, inter-annual variability of the model’s performance is observed reflecting the hydrographic changes occurred in the wider area during the study period. Overall, the results present the strong points but also highlight the weaknesses of the model. They also confirm the challenging task of producing high resolution numerical simulations in transitional areas such as the Ionian Sea.